The Structural Framework, Implementation Strategies and Students’ Perception of Team Based Learning in Undergraduate Medical Education of a Medical School in Malaysia - Mohd Salami, Ibrahim; Shahid, Hassan; Nabiha Gul, Hassan (2018)
Delivery and implementation strategies are key to curriculum success. There is growing evidence that team-based learning (TBL) is an effective way of interactive teaching. TBL is a method that uses learning teams to enhance student engagement and quality of learning. Individual accountability for out-of-class reading is followed by individual and group assessment. In-class application exercises, which is the hallmark of team-based learning promotes both learning and team development. TBL uses educational principles of transforming traditional content into application of knowledge and problem solving skills in an interactive learning environment. To experience the structural framework and to determine the students’ perception about TBL in clinical setting of MBBS program in a Malaysian medical school. A total of 120 students assigned to 22 small subgroups of 5–6 per group underwent a number of TBL sessions delivered in three phases. In Phase I, students were assigned reading material. In Phase II, students were assessed through One Best Answer (OBA) items for individual and group readiness assessment test as individual readiness assessment test (IRAT) and group readiness assurance test (GRAT) respectively followed by a mini-lecture. In Phase III, in-class application of learning activity was performed. Finally, peer assessment evaluated the contribution of peer in TBL. A TBL Classroom Evaluation Inventory (TBLCEI) developed to probe student’s perception of TBL, comprised of 40 items composite scale with Cronbach’s alpha at 0.881. In addition, students were asked to provide their estimated grade in end of the posting assessment. Grades were categorised into excellent pass >85%, high pass 70%– 84%; average to good pass 50%–69% and fail <50%. These grades were measured against students’ TBLCEI survey score using analysis of variance (ANOVA). Results were considered significant at p < 0.05. Results of one-way analysis of TBLCEI scores differed significantly across four estimated end of posting achievers groups, F (3,116) = 52.279, p < 0.001. Bonferroni’s procedure of multiple comparisons indicated that mean value of TBLCEI score of excellent pass significantly higher [70.90 (3.684)] than high pass [66.57 (3.625)], average to good pass [60.42 (3.583)] and fail [57.67 (5.626)] at p < 0.001. It is concluded that medical students favourably liked TBL for interactive learning irrespective of their grades. A positive response for TBL from students is encouraging to consider switching over from traditional lecture to TBL in curriculum delivery. The students in TBL practice also delightfully embraced immediate feedback assessment technique (IF-AT) for partial credit based on number of attempts and selection of correct answer that was used in current study to score OBA in GRAT.